From the metropolitan area to the urban sprawl: the patchiness of the territory - Mazzeo, Giuseppe (TeMA - Journal of Land Use, Mobility and Environment, 2010)
The paper tackles the phenomenon of the urban expansion through two concepts: metropolitan area and sprawl. The first, heir of the rational and positivist tradition of development, would lead to orderly and efficient metropolis; the second, son of the capitalist individualism and of the environmentalist emergency, considers the expanded city as one of the symbols of the process of unlimited appropriation of the space. Between these two concepts there is the short period of last crisis of the city, the two decades from 1970s to 1980s. From this moment the city is emerged acting out towards three main directions: the first is the expulsion of activities considered unessential; the second is the repossession of abandoned parts of the city and their transformation into high quality urban districts; the third is the search for new meanings and new perspectives, with the following marketing actions that appear to be central in the city’s policies. In this process it is interesting to observe that the actions regarded as positive are physically positioned in different places from the negative ones: when one talk about urban rehabilitation the mind runs to downtown or to semi-central urban areas; the same when one talk about actions on the image of the city. The final section of the paper examines the metropolitan area of Naples. The analysis is conducted by a qualitative point of view (in relation to the functional character of the metropolitan area) and by a quantitative point of view (in relation to the changes of the population structure over the past 150 years). In this regard, the “analytical metropolitan area” has nothing to do with the potential administrative boundaries.